2018
DOI: 10.1007/s40266-018-0591-x
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Estrogen Use and Discontinuation After Alzheimer’s Disease Diagnosis in Finland 2005–2012: A Nationwide Exposure-Matched Cohort Study

Abstract: BackgroundIt is unknown whether cognitive status or diagnosed cognitive decline affects estrogen use.ObjectivesWe assessed how common systemic estrogen use was among community-dwellers with Alzheimer’s disease (AD) and a matched comparison cohort without AD.MethodsThis study included an exposure-matched cohort of all Finnish community-dwelling women who received a clinically verified diagnosis of AD in 2005–2011 (N = 46,116; index cases) and an equally sized matched comparison cohort without AD. Follow-up bega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…1 ). Details of each study included in the analysis are listed in Supplementary Table 1 [ [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] ].…”
Section: Resultsmentioning
confidence: 99%
“…1 ). Details of each study included in the analysis are listed in Supplementary Table 1 [ [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] ].…”
Section: Resultsmentioning
confidence: 99%
“…Although possibly beneficial if taken during a critical window near menopause, estrogens therapy (especially opposed compounds) initiated in later life may be associated with increased risk in A.D. Placebo-controlled trials reported an increased risk of the incidence of dementia in women who received a conjugated equine estrogen independently from the association of medroxyprogesterone acetate [ 40 ]. Tolppanen et al [ 41 ] did not find any differences in systemic estrogen use among Finnish women with AD than those without AD. The relation of AD risk to timing and type of hormone replacement deserves further study [ 42 ].…”
Section: The Role Of Estradiolmentioning
confidence: 99%